How should central banks react to household inflation heterogeneity? - Ulrike Neyer; Daniel Stempel (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2022)
Empirical evidence suggests that considerable differentials in inflation rates exist across households. This paper investigates how central banks should react to household inflation heterogeneity in a tractable New Keynesian model. We include two households that differ in their consumer price inflation rates after adverse shocks. The central bank reacts to either an average of the households' consumer price inflation rates or their individual rates, respectively. After a negative demand shock, the consumer price inflation rates of both households diverge less from their steady states when the central bank only considers the individual inflation rate of the household experiencing the higher inflation rate. Furthermore, output fluctuates less under that regime. After a negative supply shock, a central bank only considering the household experiencing the higher inflation rate mitigates the immediate effects of the shock on both consumer price inflation rates more effectively. Our results imply that central banks, which react discretionarily to differing inflation experiences in an economy, lead to a more efficient attainment of an economy-wide inflation target and to lower fluctuations of all inflation rates.
Keywords: E31; E32; E52; 330; Business cycles; inflation; inequality; household heterogeneity; New Keynesian models